Microfluidic Oxidation of Graphite in Two Minutes with Capability of Real‐Time Monitoring. Issue 15 (2nd March 2022) - Ye, Chuanren; Wang, Gang; Yuan, Hong; Li, Jieyun; Ni, Kun; Pan, Fei; Guo, Minghao; Wu, Yanhong; Ji, Hengxing; Zhang, Fan; Qu, Bill; Tang, Zhiyong; et al.
Abstract: Graphite oxide and its exfoliated counterpart, graphene oxide, are important precursors for the large‐scale production of graphene‐based materials and many relevant applications. The current batch‐style preparation of graphite oxide suffers from safety concern, long reaction time, and nonuniform product quality, due to the large volume of reactors and slow energy exchange. Reaction in microchannels can largely enhance the oxidization efficiency of graphite due to the enhanced mass transfer and extremely quick energy exchange, by which the controllable oxidization of graphite is achieved in ≈2 min. Comprehensive characterizations show that the graphene oxide obtained through the microfluidic strategy has features like those prepared in laboratory beakers and industrial reactors, yet with the higher oxidization degree and more epoxy groups. More importantly, the microfluidic preparation allows for on‐line monitoring of the oxidization by Raman spectroscopy, ready for the dynamical control of reaction condition and product quality. The capability of continuous preparation is also demonstrated by showing the assembly of fibers and reduction of graphene oxide in microfluidic channels, and the applicability of graphene oxide prepared from the microfluidic strategy for thermally and electrically conductive films. Abstract : A continuous flow preparation of graphite oxide and the following post‐treatment are achieved in microchannels, allowing the completion of the oxidization in ≈2 min and the capability of on‐line monitoring of the oxidation process with Raman spectroscopy.